STUDY OF SEROPREVALENCE OF HEPATITIS B VIRUS INFECTION. - Yadav, Chanchal; Mane , Pratibha; Singla, Pooja; Sangwan, Jyoti (Journal of Biomedical and Pharmaceutical Research, 2021)
Introduction: HBV is a DNA virus belonging to family Hepadnaviridae. HBV infection leads to a wide spectrumof liver diseases ranging from acute to chronic hepatitis, cirrhosis & hepatocellular carcinoma. HBV is knownto be the 10th leading cause of death. WHO estimates that worldwide more than 2 billion people have beeninfected with HBV. India accounts for a very large proportion of the HBV burden.Aim and objectives: To study the seroprevalence of Hepatitis B virus infection among patients attending ourhospital, to know the prevalence among different age groups and among different gendersMaterial and Methods: This is a retrospective, cross-sectional study carried out at Dept. of Microbiology,SHKM Govt. Medical College and hospital, Nalhar, Nuh, Haryana for the duration of 6 months (April 2019 toSeptember 2019). A total of 9000 serum samples collected from patients attending outpatient departments,indoor patients and Intensive care unit of SHKM hospital.Results: It was seen that out of 9000 patients, 432 patients were positive for HBsAg with the prevalence rate4.8%. The prevalence was higher in females (5.58%) as compared to males (4.19%). The frequency of HBVamong age group 1-14, 15-40 and > 40 years was 8.4% (36), 48.3% (209) and 43.3% (187) respectively.Conclusion: Our study highlights HBV infection rate in this part of Haryana and shall provide reference tofuture studies on the epidemiology of HBV infection. It helps us to understand and assess the magnitude ofdisease in the community.Keywords: Seroprevalence, Hepatitis B, Haryana